PENGARUH FREKUENSI APLIKASI NPK YARAMILA DAN JARAK TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TERUNG (Solanum Melongena. L) - Khairunna Khairunna (Jurnal Agrotek Lestari, 2018)
This study aims to determine the effect of NPK Yaramila application frequency and plant spacing on the growth and yield of eggplant (Solanum Melongena L) and the real or not the interaction between the two factors. The experimental design used in this study was Randomized Block Design (RAK) 3 x 3 factorial pattern with 3 replications, there were 2 Factors studied were: first factor of NPK Yaramila (F) fertilization frequency with 3 levels ie 1, 2 and 3 times giving. The second factor of plant spacing (J) consists of 3 levels, namely: 60 x 60 cm, 60 x 70 cm, and 60 x 80 cm. Observation parameters observed were plant height, stem diameter, number of fruit crop, fruit weight, and fruit diameter. This research was conducted at Experimental Garden of Agriculture Faculty of Malikul Saleh Lhokseumawe University from May to July 2016. The results showed that the frequency of fertilization NPK yaramila significantly affect the plant height aged 15, 30 and 45 HST, stem diameter aged 15 and 30 HST, the number of fruit sample size, fruit weight, fruit diameter but no significant effect on stem diameter of age 45 HST. Planting rate has significant effect on plant height of 45 HST, stem diameter of 30 HST, number of sample crop, fruit weight, fruit diameter but no significant effect against plant height aged 15 and 30 HST, stem diameter aged 15 and 45 HST. The influence of interaction on eggplant diameter Keywords: Frequency of Fertilizer, Planting Distance, Eggplant